High risk behavior for HIV transmission among former injecting drug users:a survey from Indonesia - Iskandar Shelly; Basar Diba; Hidayat Teddy; Siregar Ike MP; Pinxten Lucas; van Crevel Reinout; Van der Ven Andre JAM; De Jong Cor AJ (BMC, 2010)
Abstract Background Injecting drug use is an increasingly important cause of HIV transmission in most countries worldwide, especially in eastern Europe, South America, and east and southeast Asia. Among people actively injecting drugs, provision of clean needles and opioid substitution reduce HIV-transmission. However, former injecting drug users (fIDUs) are often overlooked as a high risk group for HIV transmission. We compared HIV risk behavior among current and former injecting drug users (IDUs) in Indonesia, which has a rapidly growing HIV-epidemic largely driven by injecting drug use. Methods Current and former IDUs were recruited by respondent driven sampling in an urban setting in Java, and interviewed regarding drug use and HIV risk behavior using the European Addiction Severity Index and the Blood Borne Virus Transmission Questionnaire. Drug use and HIV transmission risk behavior were compared between current IDUs and former IDUs, using the Mann-Whitney and Pearson Chi-square test. Results Ninety-two out of 210 participants (44%) were self reported former IDUs. Risk behavior related to sex, tattooing or piercing was common among current as well as former IDUs, 13% of former IDUs were still exposed to contaminated injecting equipment. HIV-infection was high among former (66%) and current (60%) IDUs. Conclusion Former IDUs may contribute significantly to the HIV-epidemic in Indonesia, and HIV-prevention should therefore also target this group, addressing sexual and other risk behavior.